THE ROLE OF FINANCIAL PERFORMANCE ON STOCK PRICES: AN EMPIRICAL STUDY OF BASIC MATERIALS COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE 2022 - 2024 - Muhammad Fajar Alamsyah Razak; Anida Almira Syahid; Muhammad Sabrian Oehoedoe; Mohammad Shiddiq; Anisah Nadya Ananta; Nur Patmasari (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study examines the effect of financial performance, measured by Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER), on the stock prices of Basic Materials companies listed on the Indonesia Stock Exchange during 2022–2024. A quantitative approach was applied using secondary data from annual reports and stock price records. Purposive sampling produced 77 companies and 231 observations. Stock price, measured using the natural logarithm of the closing price, was analyzed through multiple linear regression. The results show that ROA has a positive and significant effect on stock prices, indicating that effective asset utilization strengthens investor confidence. Meanwhile, ROE and DER have no significant partial effect on stock prices. However, ROA, ROE, and DER simultaneously significantly affect stock prices. The study concludes that financial performance influences stock prices, primarily through asset management efficiency. Future studies may include additional financial and macroeconomic variables.